The Effect of Antioxidants Uses with Aminoglycosides Antibiotics on Serum Creatinine and Urea Levels - Purnasari, Cahyani (Indonesian Journal of Clinical Pharmacy, 2024)
Aminoglycosides are older-generation antibiotics used to treat infectious diseases like tuberculosis and urinary tract infections. While they improve multidrug resistant tuberculosis treatment success, their nephrotoxicity hinders optimal therapy. This study investigated the concomitant use of aminoglycosides (streptomycin, gentamicin, and kanamycin) and antioxidants to mitigate nephrotoxicity, as measured by serum creatinine and urea levels. Using a retrospective, descriptive analytical design, we analyzed medical records of 32 patients treated with aminoglycoside antibiotics at dr. Wahidin Sudirohusodo Hospital, Makassar, from January 2017 to November 2018. Patients were grouped based on antioxidant treatment: N-acetylcysteine (NAC), N-acetylcysteine and Curcuma (NAC+Cur), vitamin C (Vit C), Curcuma and vitamin C (Cur+Vit C), and a control group (X) receiving no antioxidants. All antioxidant groups showed decreased creatinine and urea levels with streptomycin, except the control group, which exhibited increased levels. With gentamicin, only vitamin C decreased urea. For kanamycin, NAC, NAC+Cur, and Cur+Vit C decreased urea, while NAC+Cur also decreased creatinine. NAC alone and the NAC+Cur combination showed the greatest ability to reduce serum creatinine and urea levels for both streptomycin and kanamycin. These findings suggest that antioxidant supplementation, particularly NAC and NAC+Cur, may play a crucial role in mitigating aminoglycoside-induced nephrotoxicity. Reduced creatinine and urea levels with antioxidant use could translate to improved renal function and potentially better patient outcomes during aminoglycoside therapy. Further research is needed to confirm these findings and explore optimal antioxidant dosing strategies in clinical practice.